1997
DOI: 10.1063/1.366097
|View full text |Cite
|
Sign up to set email alerts
|

Efficient multilayer electroluminescence devices with poly(m-phenylenevinylene-co-2,5-dioctyloxy-p-phenylenevinylene) as the emissive layer

Abstract: The use of a new highly luminescent conjugated polymer as an emissive layer in single and multilayer electroluminescence devices is reported. Poly(m-phenylenevinylene-co-2,5 -dioctyloxy-p-phenylenevinylene) [PmPV-co-DOctOPV] was prepared via a Wittig synthesis reaction. The resulting polymer has a high photoluminescence quantum efficiency in the solid state with an emission spectrum peaked at 506 nm (2.45 eV) in the green. Electroluminescence devices were fabricated with an ITO anode and a MgAg cathode. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(45 citation statements)
references
References 54 publications
1
44
0
Order By: Relevance
“…Previously, it was shown that the change in backbone configuration blue shifts the absorption and luminescence as expected [13][14]. It may also be expected that the geometry of the backbone reduce the distances over which phonons can propagate.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was shown that the change in backbone configuration blue shifts the absorption and luminescence as expected [13][14]. It may also be expected that the geometry of the backbone reduce the distances over which phonons can propagate.…”
Section: Introductionmentioning
confidence: 99%
“…A blue shift of the absorption and PL maxima compared to the corresponding all paraphenylenevinylene copolymer has been observed. 11 The PmPV used in this work was synthesized by the Organic Materials Synthesis section of Materials Ireland Polymer Research Center in Trinity College Dublin. 12 Two different synthesis reactions have been used with three solvents to give six different synthesis pathways for the polymer.…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…Since PLEDs require injection of both electrons and holes into the active material, balancing charge flow is essential to increase device efficiency. [2] The majority of electroluminescent polymers used as active materials have higher hole mobilities than electron mobilities, in addition to an incompatibility between their low LUMO levels and the high work function metallic cathodes used. [3,4] Thus significant interest towards increasing charge flow balance has focused on improving electron injection at the cathode/polymer interface.…”
Section: Introductionmentioning
confidence: 99%